Pendidikan Inklusif Di Indonesia: Alternatif Penguatan Model Sistem Pendidikan - Arif Syamsurrijal (LPPM Institut Agama Islam Al-Hikmah Tuban, 2019)
Abstract, Education becomes an important part for the survival of a nation, and Education for children has become an obligation to be considered. Indonesia is a country with various tribes, religions, and cultures, where everyone in it has the same rights and obligations before the Indonesian state. There is nothing that needs to be distinguished because each of these components has its own characteristics and special features. This of course also applies in the world of Education, where every child, or everyone has the same right to get Education. Of course, this also applies to those who have special needs. Juridically, education for children with special needs (ABK) is regulated in: The 1945 Constitution of the Republic of Indonesia (RI), there are articles on human rights. The Development of a National Inclusive Education Development Master Plan for 2019-2024 was arranged based on seven components, each component being an interrelated and inseparable part. These components are: theme, macro objectives, program scope, achievement strategies, outputs and outcomes, evaluation and monitoring, and targets.Keywords: education, inclusive education, Indonesia